2015
DOI: 10.1007/s10668-015-9690-6
|View full text |Cite
|
Sign up to set email alerts
|

Fishers’ perceptions of climate change, impacts on their livelihoods and adaptation strategies in environmental change hotspots: a case of Lake Wamala, Uganda

Abstract: Fisheries resources support livelihoods of fishing communities but are threatened by over-exploitation, habitat degradation, pollution, invasive species and climate change. Unlike the other threats, climate change has received limited consideration and reducing its risks requires appropriate adaptation strategies. This study used quantitative and qualitative methods to generate knowledge on fishers' perceptions of climate change, changes in climate variables and their impacts on livelihoods, adaptation strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 31 publications
4
50
1
1
Order By: Relevance
“…In South America, research has only been conducted on fishers’ perceptions of birds biology [46], the interaction between birds and fishing [47], and territorial use rights [48]. However, the study contributes to the global literature of fishers’ perceptions of environmental change [49–52], and similar results were recorded by West and Vásquez-León [53] and Puri [54] for farmer’s perception of meteorological records.…”
Section: Discussionsupporting
confidence: 53%
“…In South America, research has only been conducted on fishers’ perceptions of birds biology [46], the interaction between birds and fishing [47], and territorial use rights [48]. However, the study contributes to the global literature of fishers’ perceptions of environmental change [49–52], and similar results were recorded by West and Vásquez-León [53] and Puri [54] for farmer’s perception of meteorological records.…”
Section: Discussionsupporting
confidence: 53%
“…Traditional ecological knowledge can help fishers find new fishing areas, switch gear types and take on other jobs (Sievanen, 2014). Musinguzi et al (2016) reported fishers in Uganda were aware of climate change and its impacts on fish harvests and responded by spending more time fishing, shifting target species and using different types of fishing gears (Musinguzi et al, 2016). Others diversified their livelihoods by engaging in crop and livestock production (Musinguzi et al, 2016).…”
Section: Livelihood Adaption Adaptive Capacity and Coping Mechanismsmentioning
confidence: 99%
“…Musinguzi et al (2016) reported fishers in Uganda were aware of climate change and its impacts on fish harvests and responded by spending more time fishing, shifting target species and using different types of fishing gears (Musinguzi et al, 2016). Others diversified their livelihoods by engaging in crop and livestock production (Musinguzi et al, 2016). Many others have turned to aquaculture to substitute demands for fish (Cooke et al, 2016).…”
Section: Livelihood Adaption Adaptive Capacity and Coping Mechanismsmentioning
confidence: 99%
“…However, using fisheries as natural insurance may require switching to alternative fish species and changing fishing grounds, as in the case of Ugandan fishers responding to increased floods and droughts (Musinguzi et al. ).…”
Section: Introductionmentioning
confidence: 99%